Growth Behaviour and Phenology of some Teak Clones - Pradhan, T. R.; Bhol, N.; Parida, A. K.; Behera, M. K. (Indian Forester, 2020)
The study was carried out in a Teak plantation of31-32 years old inside the Silvicultural Research Station, Koshia in Angui district of Odisha during January 2013 to June 14 to assess the growth behaviour and phenology of selected teak clones. The trial consists of 15 plus trees ofPurunakote and Barbara provenances of Odisha. The clone ORPUB 18 exhibited maximum DBH (26.60 and 28.01 cm) and height (19.45 and 19.46 m) at 31 and 32 years age, respectively among the clones. The lowest DBH of 19.22 and 20.61 cm and height o f 15.23 and 15.31 m were found in clone ORPUB 13 in 31 and 32 years of age, respectively. The phenology of ORPUB21 was observed earlier as compared to other clones. The peak ieafshedding ofdifferent clones was noticed between 3rd week ofDecemberto last week of January. Between the month of April to Mayieafrenewai in different clones occurred. The peak flowering ofciones was observed in last week of July to 1st week ofSeptember. Time of peak fruiting and peak fruit fail occurred in 1st week ofSeptember to last week ofOctober and 3rd week of December to last week ofJanuary, respectively. The variations in the diameter and height growth were indicating that these parameters are under genetic control whereas duration of different phenoiogicai events is influenced by environmental factors.